Post-synthetic modification of metal–organic frameworks - Abdelhameed, Reda Mohamed (2016)
Post-synthetic modification (PSM) of metal-organic frameworks encompassing the chemical transformation of the linker present is a promising new route for engineering optical centres and tuning the light emission properties of materials, both in the visible and in the near infrared (NIR) spectral regions. Here, PSM of isoreticular metal-organic framework-3 (IRMOF-3) with ethyl oxalyl monochloride, ethyl acetoacetate, pentane-2,4-dione, 3-(2- hydroxyphenyl)-3-oxopropanal, 2-chloroacetic acid, glyoxylic acid, methyl vinyl ketone and diethyl (ethoxymethylene)malonate followed by chelation of trivalent lanthanide ions afforded intriguing near infrared (Nd3+) and visible (Eu3+, Tb3+) light emitters. IRMOF-3 was used as a case in point due to both its highly porous crystalline structure and the presence of non-coordinating amino groups on the benzenedicarboxylate (bdc) linker amenable to modification. The materials were characterised by elemental analysis, powder X-ray diffraction, optical, scanning and transmission electron microscopy, Fourier transform infrared spectroscopy, and liquid and solid-state nuclear magnetic resonance. The solid-state luminescence properties of Ln-modified-IRMOF-3 were investigated at room temperature. The presence of the bdc aromatic ring, β– diketonate and oxalate enhanced the Ln3+ sensitization via ligand-to-metal energy transfer (anthena effect). As far as photocalysis is concerned, we have synthesized metal−organic frameworks (Cr-MIL-125-AC, Ag-MIL-125-AC) by a green method (solid–vapors reactions). The resulting functionalized materials show a photocatalytic activity for methylene blue degradation up to 6.52 times larger than that of the commercial photocatalyst hombikat UV-100. These findings open the door for further research for improving the photocatalytic performance of metal-organic frameworks.